Penerapan Nilai-Nilai Positif Olahraga pada Kehidupan Sosial Siswa - Hamidi, Ahmad (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study. This study aims to determine the extent of the application of the positive values of sports in students' social life. Materials and methods. This study describes the application of the positive values of sports to students of SMP Negeri 1 Takokak, Cianjur Regency. The method used in this research is a survey method, and the data collection technique uses a questionnaire. The variable in this study is the application of the positive values of sports to students at SMP Negeri 1 Takokak, Cianjur Regency. The application of positive values in question is the attitudes possessed by students that apply in general social life. Measured through a questionnaire with the following factors: Internal factors, including: discipline, responsibility, sportsmanship. External factors, including: cooperation, mutual respect and help. Results. Based on the distribution table of the categorization of the application of positive sports values, 8 respondents (6.67%) had the